A 49-Kilodalton Isoform of the Adenovirus Type 5 Early Region 1B 55-Kilodalton Protein Is Sufficient To Support Virus Replication - Kindsmüller, Kathrin (American Society for Microbiology (ASM), 2009)
The adenovirus type 5 (Ad5) early region 1B 55-kDa (E1B-55K) protein is a multifunctional regulator of cell-cycle-independent virus replication that participates in many processes required for maximal virus production. As part of a study of E1B-55K function, we generated the Ad5 mutant H5pm4133, carrying stop codons after the second and seventh codons of the E1B reading frame, thereby eliminating synthesis of the full-length 55K product and its smaller derivatives. Unexpectedly, phenotypic studies revealed that H5pm4133 fully exhibits the characteristics of wild-type (wt) Ad5 in all assays tested. Immunoblot analyses demonstrated that H5pm4133 and wt Ad5 produce very low levels of two distinct polypeptides in the 48- to 49-kDa range, which lack the amino-terminal region but contain segments from the central and carboxy-terminal part of the 55K protein. Genetic and biochemical studies with different Ad5 mutants show that at least one of these isoforms consists of two closely migrating polypeptides of 433 amino acid residues (433R) and 422R, which are produced by translation initiation at two downstream AUG codons of the 55K reading frame. Significantly, a virus mutant producing low levels of the 433R isoform alone replicated to levels comparable to those of wt Ad5, demonstrating that this polypeptide provides essentially all functions of E1B-55K required to promote maximal virus growth in human tumor cells. Altogether, these results extend previous findings that the wt Ad5 E1B region encodes a series of smaller isoforms of E1B-55K and demonstrate that very low levels of at least one of these novel proteins (E1B-433R) are sufficient for a productive infection.